GE_GERICHTE P/15396/2021 vom 10. Mai 2023 - GE Cour de justice (2023)
USURE(DROIT PÉNAL);TRAITE D'ÊTRES HUMAINS;VOL(DROIT PÉNAL);ABUS DE CONFIANCE;PROCÈS-VERBAL;RECTIFICATION(EN GÉNÉRAL);DÉLAI;DROIT D'ÊTRE ENTENDU | CP.157; CP.182; LEI.116; LAVS.87; CPP.79; CPP.80.al3; CPP.78.al5; Cst.29.al2